A maximal rowing ergometer protocol to predict maximal oxygen uptake - Jensen, K.; Frydkjær, M.; Jensen, N. M. B.; Bannerholt, L. M.; Gam, S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the relationship between the maximal power output (MPO) in an individualized 7 × 2-minute incremental (INCR) test, average power in a 2k (W2k) rowing ergometer test, and maximal oxygen uptake (V.O2max) and to develop a regression equation to predict V.O2max. Methods: A total of 34 male club rowers (age 18-30 y) performed a 2k and an INCR test in a Concept2 rowing ergometer to determine and compare MPO, W2k, and V.O2max. Results: No significant difference was found between V.O2max measured during INCR or 2k test (P = .73). A very high correlation coefficient (r = .96) was found between MPO and V.O2max and between W2k and V.O2max (r = .93). Linear regression analyses were developed for predicting V.O2max from MPO: (1) V.O2max (L/min)) = 11.49 × MPO + 810 and V.O2max from W2k: (2) V.O2max = 10.96 × W2k + 1168. Cross-validation analyses were performed using an independent sample of 14 rowers. There was no difference between the mean predicted ?VO2max in the INCR test (4.41 L·min-1) or the 2k test (4.39 L/min) and the observed V.O2max (4.40 L/min)). Technical error of measurement was 3.1% and 3.6%, standard error of estimate was 0.136 and 0.157 L/min), and validation coefficients (r) were .95 and .94 using Equation () and (), respectively. Conclusion: A prediction model only including MPO or W2k explains 88% to 90% of the variability in V.O2max and is suggested for practical use in male club rowers.